Implementation Of Implementation Of Providing Legal Assistance For Disappointed Communities In The View Of Islamic Law - Aini, Rinda Kuratul (Politeknik Siber Cerdika Internasional, 2023)
The purpose of this study is to describe the application of 3 character values through planning analysis, learning implementation and learning evaluation as well as to determine the supporting and inhibiting factors of the application of 3 character values in grade IV SDN Tiwu Asem. This research includes qualitative descriptive data taken through in-depth interviews with resource persons, in addition to data collection techniques through field observation and documentation. The validity of the data used is by source triangulation, technical triangulation and theory triangulation. Data analysis techniques are carried out by collecting data, reducing data, presenting data and drawing conclusions. The results showed that the application of the character values of SDN Tiwu Asem has been integrated into learning through the process of planning, implementation and evaluation as well as through applicable habituation. The supporting factor is the content of character education in the curriculum and also the driving teacher as a support in the application of character values. While the inhibiting factors are the lack of aspects of teacher understanding, student behavior, learning implementation and the lack of school culture to support character education.